Facile and Rapid Oxidation Fabrication of BiOCl Hierarchical Nanostructures with Enhanced Photocatalytic Properties. Issue 29 (4th June 2013) - Xiong, Jinyan; Jiao, Zhengbo; Lu, Gongxuan; Ren, Wei; Ye, Jinhua; Bi, Yingpu
<x xml:space="preserve">Abstract</x> Coming up flowers: Three‐dimensional (3D) flower‐like BiOCl hierarchical nanostructures (HNs) were fabricated by a facile and rapid in situ oxidation reaction between metallic Bi nanospheres and FeCl3 at room temperature (see scheme). These structures exhibit excellent photocatalytic activity for rhodamine B degradation and photoelectric conversion properties.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>